Unveiling the Dynamics: An Inclusive Study on How Social Media is Impacting Purchase Intentions in the Ever-Evolving Travel World - Khan, Safdar; Rehman, Asad; Zaman, Omama (ASEAN Journal on Hospitality and Tourism, 2025)
This research explores the notable changes brought about by“social media on consumers' buying intentions in the travel sector. To achieve this, we utilized Davis's Technology Acceptance Model (TAM) from 1989, while introducing two additional factors: Trust and Tourists' Motivation, alongside Electronic Word-of-Mouth (E-WOM). The study employed a convenience sampling method and gathered data through an online survey instrument. Participants included Indian customers, and the collected data was analyzed using PLS 4.0 software. Results indicate that integrating TAM with elements of tourist motivation, trust, and E-WOM provides a robust framework for understanding how social media is shaping purchase intentions in the dynamic travel industry. The study highlights the necessity for further investigation into this topic, which will enhance our comprehension of the various factors influencing how social media impacts purchasing intentions in the continually evolving travel landscape. It is important to note that the research is focused solely on the Indian market. This research stands out by specifically examining the role of social media in influencing purchase intentions within the travel sector. Although social media has been extensively studied in other areas like fashion and hospitality, this study contributes a new perspective on its empathetic effects.